Freedom of creativity: from the text of O. Dovzhenko to the film by Y. Solntseva («Poems about the sea») - Кузьменко, Наталя Станіславівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article deals with the problem of understanding and interpreting the word «freedom» in Soviet Union on the example of the film script by O. Dovzhenko and its implementation in the cinema - a film by Y. Solntseva «The Poem about the Sea». We used discourse and descriptive methods, which allowed to analyze the opposition «text – film» and «Dovzhenko – Solntseva» taking into account extralinguistic factors. These factors determine social relationships, geography, gender, cultural influences, and they have become the cause of the differentiation of the views of artists and, consequently, the differences between the film and the script. Some aspects of the differences between works are systematized (change of language, composition of actors, locations of shooting, manners of narrative of the text, etc.). We based our assumptions on the diary entries of the artist, his correspondence, on the letters of the actors and his friends. Conclusions are made regarding the propaganda motives of the film, as well as their analysis. Y. Solntseva intensifies his attention to the problems of heroization, the rise of Soviet culture and the importance of building communism, and for O. Dovzhenko the main thing was the truthfulness of the depicted sceneries, the scale and volume of the frame.